2014
DOI: 10.1371/journal.pone.0094535
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Foot Arch Volumes and Dynamic Plantar Pressure during Midstance of Walking in Preschool Children

Abstract: ObjectivesThe purpose of this study was to examine the correlation between the foot arch volume measured from static positions and the plantar pressure distribution during walking.MethodsA total of 27 children, two to six years of age, were included in this study. Measurements of static foot posture were obtained, including navicular height and foot arch volume in sitting and standing positions. Plantar pressure, force and contact areas under ten different regions of the foot were obtained during walking.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 28 publications
2
26
0
2
Order By: Relevance
“…The peaks were high in the hallux region, low in the midfoot region and metatarsals and absent in the heel region (30,31) in both feet. Gaston et al (27) found a correlation between the rotation of the foot and of the hip and pelvis, showing that when the foot receives the load medially, the entirety of the lower limb rotates inward.…”
Section: Discussionmentioning
confidence: 91%
“…The peaks were high in the hallux region, low in the midfoot region and metatarsals and absent in the heel region (30,31) in both feet. Gaston et al (27) found a correlation between the rotation of the foot and of the hip and pelvis, showing that when the foot receives the load medially, the entirety of the lower limb rotates inward.…”
Section: Discussionmentioning
confidence: 91%
“…Lastly, the forefoot push-off phase (FFPOP) starts when the metatarsal heads and the toes are the only support in contact with the ground. The toe-off event is considered the transition between the stance and swing phases [13,17].…”
mentioning
confidence: 99%
“…The correlation between the measured and predicted speed varies between 0.950 and 0.978 depending on the gait speed (slow, normal or fast walking). Chang et al investigated the correlation between different foot arch measures and the plantar pressure [2]. A correlation of 0.32 was found between the arch volume index and the change in pressure under the midfoot.…”
Section: Discussionmentioning
confidence: 99%